Barriers and conditions of open operation: a customer perspective on value co-creation for integrated product-service solutions. (2017) - Sjödin, David Rönnberg; Parida, Vinit; Lindström, John
Enabling value co-creation between provider and customer is a key requirement for successful adoption of integrated product-service offerings in a capital good industrial setting. However, little is known about the barriers and conditions explaining customer's willingness to 'open up' their internal processes for value co-creation with providers. Based on a multiple exploratory case studies with four customers and four providers within the manufacturing and process industries, this study identifies three barriers to open operation (operational cultural resistance, loss of operational know-how and risk of operational conflict) which may restrict the potential for increased value co-creation and must be managed to support the adoption of integrated solutions. In addition, we identify two key conditions related to the criticality of the operational process and the state of operational competences as strong influences for which form of open operation engagement would be favoured by customer. The study holds both theoretical and practical implications.